1981
DOI: 10.1093/cvr/15.12.680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischaemia on the adrenergic neurons of the rat heart: a fluorescence histochemical and biochemical study

Abstract: Left coronary artery ligation was performed in pentobarbitone anaesthetised rats. Following 1/2 and 2 1/2 h of coronary artery occlusion or sham-operation the right and left ventricular myocardium and the interventricular septum were analysed for tissue content of catecholamines. In control rats and in rats with coronary artery ligation for various time periods (1/2, 2 1/2 and 5 h), the Hillarp-Falck fluorescence histochemical technique was used to visualise the catecholamines of the ventricular myocardium. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…It has also previously been demonstrated that myocardial ischaemia causes a marked increase in noradrenaline over¯ow (Wennmalm, 1977;SchroÈ r et al, 1981a), probably due to a redistribution of noradrenaline from its storage sites in adrenergic nerve terminals into the extraneuronal space (Holmgren et al, 1981;SchroÈ r et al, 1981a;Muntz et al, 1984) which is initiated by enhanced exocytosis at short-term ischaemia (SchoÈ mig et al, 1984). This process is enhanced by nicotine (SchoÈ mig et al, 1987;KruÈ ger et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has also previously been demonstrated that myocardial ischaemia causes a marked increase in noradrenaline over¯ow (Wennmalm, 1977;SchroÈ r et al, 1981a), probably due to a redistribution of noradrenaline from its storage sites in adrenergic nerve terminals into the extraneuronal space (Holmgren et al, 1981;SchroÈ r et al, 1981a;Muntz et al, 1984) which is initiated by enhanced exocytosis at short-term ischaemia (SchoÈ mig et al, 1984). This process is enhanced by nicotine (SchoÈ mig et al, 1987;KruÈ ger et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…This catecholamine over¯ow during longer periods of ischaemia (i.e. 410 min) results in a redistribution of catecholamines in the ischaemic area of the ventricle (Holmgren et al, 1981;SchroÈ r et al, 1981a;Muntz et al, 1984) and is initiated by intraneuronal release of catecholamines from their storage vesicles (SchoÈ mig, 1990). Thus, nicotine-induced catecholamine release might stimulate the ischaemia-related catecholamine over¯ow and increase the severity of myocardial ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…In skeletal muscle, morphologic evidence of ischemic damage can be seen in sympathetic nerves after 2 h of ischemia, while ischemic changes in myocytes are not evident until at least 3 h (16). In rabbit heart, partial depletion of myocardial catecholamine stores becomes evident after only 30 min of ischemia, and progresses to near total depletion after 2.5-5 h (17).…”
Section: Methodsmentioning
confidence: 98%
“…Postmortem analyses of infarcted human myocardium show abnormal increases in numbers of sympathetic axons adjacent to the site of injury (Cao, et al, 2000a). Ischemic injury appears to be the cause of the remodeling, as coronary artery ligation induces hyperinnervation in dogs (Lai, et al, 2000;Zhou, et al, 2004) and rats (Ahonen, et al, 1975;Paessens and Borchard, 1980;Holmgren, et al, 1981;Vracko, et al, 1990;Kaye, et al, 2000;Li, et al, 2004). Through enhanced norepinephrine-mediated myocardial depolarization, abnormally increased sympathetic nerve density may be proarrhythmogenic and represent a significant factor in post-infarct sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%